Preparation method of novel photocatalytic material Bi2O2SO4 / Bi, N, S-TiO2

By doping Bi, N and S on TiO2 to prepare Bi2O2SO4/Bi, N, S-TiO2 composite photocatalytic materials, the problem of TiO2 poor response ability to visible light is solved, efficient degradation of trichloroethylene and PMS activation are achieved, and the preparation cost is reduced.

CN120132881APending Publication Date: 2025-06-13INNER MONGOLIA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054676.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

As a photocatalyst, TiO2 has problems with poor ability to respond to visible light and low photogenerated carrier separation efficiency, making it difficult to effectively activate persulfate, which limits its application in practice.

Method used

Bi2O2SO4/Bi,N,S-TiO2 composite photocatalytic materials were prepared by sol-gel method and calcination method. The utilization ability of TiO2 to visible light was improved by doping Bi, N and S, and the adsorption and activation of PMS were enhanced by deposition of BOS.

Benefits of technology

The efficient degradation rate of trichloroethylene (TCE) under visible light irradiation of LED lamps is achieved, reaching 93%, and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005241035440000011
    Figure HDA0005241035440000011
  • Figure HDA0005241035440000021
    Figure HDA0005241035440000021
  • Figure HDA0005241035440000031
    Figure HDA0005241035440000031
Patent Text Reader

Abstract

The invention provides a preparation method of a novel photocatalytic material Bi2O2SO4 / Bi, N, S-TiO2, and belongs to the field of inorganic catalytic materials. The composite photocatalyst Bi2O2SO4 / Bi, N, S-TiO2 is prepared by adopting a sol-gel method, the preparation process is simple, the equipment requirement is low, and the production cost is low. The novel photocatalytic material is a heterojunction material composed of Bi2O2SO4 and TiO2 doped with three elements of Bi, N and S. The invention further discloses a preparation method of the novel photocatalytic material. The PMS (peroxymonosulfate KHSO5 is greater than or equal to 42%, and KHSO5.0.5 KHSO4.0.5 K2SO4) has good capability of degrading organic pollutants by activating PMS (peroxymonosulfate KHSO5 is greater than or equal to 42%, KHSO5.0.5 Under the irradiation of visible light, when a trichloroethylene (TCE) solution with the concentration of 7 mg / L is used as a substrate, the degradation rate reaches 93% in 30 min, the catalyst concentration is 1.5 g / L, and the PMS concentration is 1.7 g / L.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method of a novel photocatalytic material Bi 2 O 2 SO 4 / Bi, N, S-TiO 2 and belongs to the technical field of inorganic catalytic materials. Background Art

[0002] Trichloroethylene (TCE) has attracted wide attention as a typical chlorinated organic pollutant. Trichloroethylene is an important organic solvent and has a wide range of uses in the industrial field, such as metal degreasing agent, extraction solution, dry cleaning detergent, etc. The usage amount of TCE in some developed countries is quite large. As a typical chlorinated hydrocarbon pollutant, TCE can cause many environmental problems, especially its carcinogenic, teratogenic and mutagenic hazards. As a common pollutant in groundwater, TCE is easily adsorbed by soil and is difficult to be degraded by traditional biochemical treatment processes, which may cause more complex environmental problems. The PMS activation technology based on sulfate radicals has strong oxidation performance and can properly solve the environmental problems caused by such refractory organic pollutants as TCE. Solar energy is a green and cheap energy source, so it is the most economical and effective method for activating persulfate technology and will not cause secondary pollution. However, PMS cannot be directly activated by visible light, and most of the energy in sunlight is in the form of visible light, so it restricts the application of photocatalytic PMS activation technology in practice. The catalyst is the most important part of the photocatalytic activation of PS process. TiO 2 has received the attention of many researchers as a photocatalyst with the longest service time and the widest application range. However, the disadvantages of TiO 2 itself restrict the application of TiO 2 , such as poor ability to respond to visible light and low separation efficiency of photo-generated carriers.

[0003] Researchers have adopted many methods to improve the photocatalytic activity of TiO 2 , such as synthesizing heterojunctions based on TiO 2 , element doping, morphology control and other methods to make up for the defects of the single component of TiO 2 materials, and prepared TiO 2 -based materials with more excellent performance. Such as "Chemical Engineering Journal", Volume 384, Page 123245, "Visible-light Activation of Persulfate by TiO 2 / g-C 3 N 4In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. 2 / g-C 3 N 4 In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. 2 In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. 2 / g-C 3 N 4 In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. 2 O 2 SO 4 In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. 2 O 2 SO 4 In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. 2 O 2 SO 4 In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. 2 O 2 SO 4 In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. 2 O 2 SO 4 In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. 2 O 2 SO 4 In the article "Photocatalyst toward Efficient Degradation of Micropollutants", TiO composites with different ratios were prepared by the sol-gel + calcination method. The disadvantages of this method are as follows: (1) Although the separation efficiency of photogenerated carriers is improved, TiO still cannot absorb visible light; (2) The prepared TiO / g-CN composites do not have the ability to adsorb persulfate. Another example is the article "Atomic interfacial structure and charge transfer mechanism on in-situ formed BiOI / BiO SO p-n heterojunctions with highly promoted photocatalysis" on page 120492, volume 297 of "Applied Catalysis B: Environmental". By using the deposition method, calcination method and hydrothermal method, the BiOI / BiO SO binary composite was successfully prepared. The problems of this method are: (1) The preparation process is relatively complex. First, BiO SO is prepared by the deposition method and calcination method, and then BiOI / BiO SO can be obtained by the hydrothermal method; (2) Although the separation efficiency of photogenerated carriers can be improved by the loading of BiO SO, the performance of the new photocatalytic material BiO SO has not been further explored. Summary of the Invention

[0004] In view of the problems of easy recombination of charge carriers and insufficient reduction ability of conduction band electrons in TiO, a composite photocatalytic material BiO SO was prepared. 2 In view of the problems of easy recombination of charge carriers and insufficient reduction ability of conduction band electrons in TiO, a composite photocatalytic material BiO SO was prepared. 2 O 2 SO 4 / Bi,N,S-TiO 2 (hereinafter abbreviated as BOS / BNST, Bi 2 O 2 SO 4 (hereinafter abbreviated as BOS) aims to obtain photocatalytic materials with better performance and investigate the degradation parameters of trichloroethylene (TCE) and shale gas in simulated wastewater. The preparation process is simple, the visible-light photocatalytic activity of the composite material is high and the cost is low, which provides technical support for the research of Bi 2 O 2 SO 4 -based visible-light photocatalytic materials and the performance of photocatalytic activation of persulfate. The preparation method of the Bi 2 O 2 SO 4 / Bi,N,S-TiO 2 composite photocatalytic material is as follows: (1) Preparation of BOS / BNST composite material Add 1.1 g of Bi(NO 3 ) 3 ·5H 2 O and 2 g of thiourea into a solution composed of 20 ml of absolute ethanol, 5 ml of deionized water and 10 ml of acetic acid, and stir with a magnetic stirrer until all the solids in the solution are dissolved. This solution is called solution A. Add 10 ml of tetrabutyl titanate (TBOT) to 20 ml of absolute ethanol to make solution B. Slowly add solution A to solution B and keep stirring to form a stable and uniform sol-gel. Transfer the final sol-gel to a hydrothermal autoclave with a polytetrafluoroethylene liner, heat it to 100 °C and keep it for 5 hours. After the hydrothermal autoclave cools to room temperature, use a centrifuge to separate the solid substances, and then wash them once with deionized water. Place the obtained solid in an oven and dry it thoroughly at 100 °C. Grind the dried solid substance with an agate mortar and transfer it to an uncovered crucible. Place the crucible in a muffle furnace and calcine it at 500 °C for 2 h. After 2 h, take out the solid, and the BOS / BNST catalyst is prepared.

[0005] (2) Preparation of BOS Add 1.1 g of Bi(NO 3 ) 3 ·5H 2 O and 2 g of thiourea into a solution composed of 20 ml of absolute ethanol, 5 ml of deionized water and 10 ml of acetic acid, and stir with a magnetic stirrer until all the solids in the solution are dissolved. Then continue stirring at 100 °C until completely dry. Transfer the dried solid to an uncovered crucible, place it in a muffle furnace and heat it at 500 °C for 2 h, and then take it out to obtain the solid of BOS.

[0006] The present invention adopts the above technical solutions and mainly has the following effects: (1) The Bi 2 O 2 SO 4 / Bi,N,S-TiO 2 composite photocatalytic material prepared by the method of the present invention has high photocatalytic activity. Under visible light irradiation (230 mW / cm 2 ) of an LED lamp (wavelength = 427 nm), when the prepared binary composite photocatalytic material is put into a solution with a TCE concentration of 7 mg / L and a PMS concentration of 1.7 g / L, after 30 minutes of visible light irradiation, the degradation rate of trichloroethylene (TCE) by this heterogeneous photocatalytic system reaches 93%.

[0007] (2) The photocatalytic material prepared by the sol-gel method and the calcination method adopted by the present invention has a simple preparation method, requires less equipment, and has a low cost.

[0008] (3) In the Bi 2 O 2 SO 4 / Bi,N,S-TiO 2 composite photocatalytic material prepared by the method of the present invention, the doping of Bi, N, and S improves the ability of titanium dioxide (TiO 2 ) to utilize visible light. The synthesis of this heterojunction improves the separation efficiency of photo-generated carriers, and the deposition of BOS helps to enhance the adsorption of PMS. The cycle of bismuth ions Bi 4+ and Bi 3+ in BOS / BNST promotes the activation of PMS. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is the X-ray diffraction pattern of Bi 2 O 2 SO 4 , TiO 2 and Bi 2 O 2 SO 4 / Bi,N,S-TiO 2 .

[0010] Figure 2 is the scanning electron microscope image of Bi 2 O 2 SO 4 , TiO 2 and Bi 2 O 2 SO 4 / Bi,N,S-TiO 2 .

[0011] Figure 3Degradation diagrams of various photocatalytic systems when trichloroethylene (TCE) is the target pollutant.

[0012] Figure 4 Degradation, current-voltage curve and power density curve diagrams of a photocatalytic fuel cell using shale gas produced water as the substrate. Detailed implementation manners

[0013] The present invention will be further described below in conjunction with the detailed implementation manners. Example 1

[0014] A preparation method of a novel composite photocatalytic material Bi 2 O 2 SO 4 / Bi, N, S-TiO 2 is as follows: 1.1 g of Bi(NO 3 ) 3 ·5H 2 O and 2 g of thiourea are added to a solution composed of 20 ml of absolute ethanol, 5 ml of deionized water and 10 ml of acetic acid, and stirred using a magnetic stirrer until all the solids in the solution are dissolved. This solution becomes Solution A. 10 ml of tetrabutyl titanate (TBOT) is added to 20 ml of absolute ethanol to make Solution B. Solution A is slowly added to Solution B with continuous stirring to form a stable and uniform sol-gel. The finally obtained sol-gel is transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner and heated to 100 °C for 5 hours. After the hydrothermal autoclave is cooled to room temperature, the solid substances are separated using a centrifuge, and then washed once with deionized water. The obtained solid is placed in an oven and dried thoroughly at 100 °C. The dried solid substance is ground using an agate mortar and then transferred to an uncovered crucible. The crucible is placed in a muffle furnace and calcined at 500 °C. After 2 hours, the solid is taken out for standby, and the BOS / BNST(1.1∶2) catalyst is prepared. Example 2

[0015] A preparation method of a novel composite photoanode material Bi 2 O 2 SO 4 / Bi, N, S-TiO 2 is as follows: 0.9 g of Bi(NO 3 ) 3 ·5H 21.3 g of Bi(NO₃)₃·5H₂O and 2 g of thiourea were added to a solution composed of 20 ml of absolute ethanol, 5 ml of deionized water and 10 ml of acetic acid, and stirred with a magnetic stirrer until all the solids in the solution were dissolved. This solution became solution A. The rest was the same as in Example 1, and the BOS / BNST(1.3∶2) catalyst was prepared. Example 3

[0016] A preparation method of a novel composite photoanode material Bi 2 O 2 SO 4 / Bi, N, S-TiO 2 is as follows: 1.3 g of Bi(NO 3 ) 3 ·5H 2 O and 2 g of thiourea were added to a solution composed of 20 ml of absolute ethanol, 5 ml of deionized water and 10 ml of acetic acid, and stirred with a magnetic stirrer until all the solids in the solution were dissolved. This solution became solution A. The rest was the same as in Example 1, and the BOS / BNST(0.9∶2) catalyst was prepared.

[0017] Experimental results The composite photocatalytic material Bi 2 O 2 SO 4 / Bi, N, S-TiO 2 prepared in Example 1 had the best catalytic performance.

[0018] The XRD pattern of TiO 2 is as shown. Diffraction peaks could be observed at diffraction angles 2θ of 25.37°, 37.88°, 48.12°, 53.97°, Figure 1 55.10°, corresponding to the (101), (004), (200), (105), (211) crystal planes of the standard card (JCPDS 86-1157), and the diffraction peaks were sharp without impurity peaks, indicating that the prepared TiO had good crystallinity. From the XRD pattern of Bi 2 O 2 SO 2 O 2 SO 4 it could also be observed that diffraction peaks could be seen at diffraction angles 2θ of 13.05°, 21.95°, 22.61°, 28.86°, 29.36°, 29.42°, 30.29° for Bi 2 O 2 SO 4The characteristic diffraction peaks correspond to the (002), (011), (-101), (013), (-103), (103), and (110) crystal planes of the standard card (JCPDS 41-0688), respectively. Moreover, the diffraction peaks are sharp without impurity peaks, indicating that the prepared Bi 2 O 2 SO 4 has good crystallinity.

[0019] In the XRD diffraction pattern of the composite material, the characteristic peaks of the (101), (004), (200), (105), and (211) crystal planes of the pure-phase TiO 2 sample can still be found. At the same time, the characteristic crystal plane peaks (-103), (103), and (110) of Bi 2 O 2 SO 4 can also be observed at 2θ of 29.36°, 29.42°, and 30.29°. And there are no other impurity peaks, indicating that Bi 2 O 2 SO 4 / Bi, N, S-TiO 2 is successfully prepared.

[0030] TiO 2 、Bi 2 O 2 SO 4 and Bi 2 O 2 SO 4 / Bi, N, S-TiO 2 The SEM images of the samples are as shown in Figure 2 Figure. As can be seen from Figure 2 (b), TiO 2 mostly presents an irregular blocky particle structure, and the sizes and thicknesses of each block are different. As can be seen from Figure 2 (c), Bi 2 O 2 SO 4 shows a flocculent structure and aggregates with each other. Figure 2 (a) is the SEM image of the composite sample Bi 2 O 2 SO 4 / Bi, N, S-TiO 2 . Many small pits appear on the irregular large-scale structure of TiO 2 , and flocculent substances of Bi 2 O 2 SO 4 are distributed in the pits.

[0031] When testing the degradation performance of a photocatalytic fuel cell using a trichloroethylene (TCE) solution as a substrate, the degradation rate of BOS / BNST (1.1:2) was the highest, reaching 93% after 30 minutes of degradation.

[0032] In the PMS-activated degradation TCE system constructed with BOS / BNST as a photocatalyst, after the reaction, it can be seen from the infrared spectrum that the prepared BOS / BNST sample formed Bi-O bonds on the surface after the reaction, so the synthesized sample has an adsorption capacity for PMS.

Claims

1. A method for preparing a novel photocatalytic material Bi2O2SO4 / Bi, N, S-TiO2, characterized in that: The specific steps are as follows: 1.1g Bi(NO3)3·5H2O and 2g thiourea were added to a solution consisting of 20ml anhydrous ethanol, 5ml deionized water and 10ml acetic acid, and stirred with a magnetic stirrer until all the solids in the solution were dissolved. The solution was called solution A. 10ml tetrabutyl titanate (TBOT) was added to 20ml anhydrous ethanol to make solution B. Solution A was slowly added to solution B and stirred continuously to form a stable and uniform sol-gel. The resulting sol-gel was transferred to a polytetrafluoroethylene-lined hydrothermal autoclave and heated to 100°C for 5 hours. After the hydrothermal autoclave was cooled to room temperature, the solid matter was separated using a centrifuge and then washed with deionized water. The resulting solid was placed in an oven and thoroughly dried at 100°C. The dried solid was ground using an agate mortar and transferred to an uncovered crucible, which was placed in a muffle furnace and calcined at 500°C. After 2 hours, the solid was taken out for use, and the preparation of Bi2O2SO4 / Bi, N, S-TiO2 catalyst was completed.